Variations in electrophysical properties of heavily doped single crystals of n-Ge 〈As〉 under the effect of thermal annealings - Gaidar, G.P. (Reports of the National Academy of Sciences of Ukraine, 2018)
Specific features of variations in the electrophysical parameters and microstructure of n-Ge single crystals doped with the arsenic impurity that occur during thermal annealings in a wide temperature range are established. The obtained dependences of the concentration and mobility of charge carriers on the annealing temperature are explained by the processes of restructuring of impurity complexes in the strongly doped germanium crystals grown by the Czochralski method.